Measuring Instagram Content Effectiveness in Digital Marketing usingthe EPIC Model and Direct Rating Method - I Gede Edy Artana; Evi Triandini; Dandy Pramana Hostiadi (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2026)
Instagram has become known as one of the leading platforms in digital marketing, making it essential to systematically evaluate the effectiveness of the content presented to ensure successful communication strategies. This study aims to measure the effectiveness of Instagram content produced by Kayana Creative using the EPIC Model and the Direct Rating Method, two complementary evaluative approaches that assess content quality and audience reception. The research involved 100 respondents who follow the Kayana Creative Instagram account. Data collected using a Likert-scale questionnaire and analyzed quantitatively to assess the four EPIC dimensions. Empathy, Persuasion, Impact, and Communication, as well as the overall evaluation through the Direct Rating Method. The results indicate that Instagram content is effective, with an average EPIC score of 4.04. The Communication dimension scored highest, indicating that the audience clearly understood the content’s messages. Using the Direct Rating Method, respondents provided an overall score of 80.48, further confirming that the content effectively captures attention and delivers a positive user experience. This study provides practical contributions for developing content that is more relevant, communicative, and engaging, and theoretical contributions by reinforcing the use of the EPIC Model and the Direct Rating Method as complementary evaluative tools for assessing content effectiveness on social media within the digital marketing context.